Personal Values in Relation to Risk Intelligence: Evidence from a Multi-Mediation Model - Andrea Zammitti; Angela Russo; Giuseppe Santisi; Paola Magnano (Behavioral Sciences, 2021)
In a risk society, personal values can be important resources, useful for managing uncertainty and guiding people in the perception of risk. The goal of this article is to explore the relationship between risk intelligence and personal values. The participants were 731 Italian adults aged between 18 and 65 years (M = 30.25; DS = 10.71). The survey was composed of the following measures: Subjective Risk Intelligence Scale and Portrait Values Questionnaire. Data analyses have found significant relationships between some types of personal values and risk intelligence: subjective risk intelligence is negatively related to conservation and positively related to openness to change and self-transcendence, but it was not related to self-enhancement. Furthermore, values of openness to change and self-transcendence mediate the relationship between age and subjective risk intelligence, while conservation values and self-enhancement values did not mediate the same relationship. Implication for practice and future research will be discussed.